(untitled) (Global Journal of Management and Business Research, 2012)
The report is based on an exploratory research on an assessment of the problems and constraints faced by small and medium-sized enterprises (SMEs) in Pakistan with regard to access to financing. The purpose of this report is to identify the core constraints in financing of SMEs in Pakistan that impede their growth and even undermine their liquidity and financial position. The research methodology includes qualitative data and quantitative data. A survey was undertaken from a sample group of 500 respondents of SMEs in Karachi from whom various questions were asked through a structured questionnaire. In addition, one-on-one formal and informal interviews were taken from various businessmen and bankers. Samples were selected conveniently. A conceptual model/framework was devised to test and ascertain the statistical validity. It includes dependent variable SME financing and independent variables, financing constraints, functional/internal barriers, government support and incentives, and SMEs growth and development.